Characteristics of youth soccer players who drop out, persist or move up - Figueiredo, António J. (2009)
In this study, we compared the growth, maturity status, functional capacity, sport-specific skill, and goal orientation of 159 male soccer players, aged 11-12 (n = 87) and 13-14 years (n = 72) years, who at follow-up 2 years later discontinued participation (dropout), continued at the same standard (club) or moved to a higher level (elite). Age group-specific multivariate analysis of variance was used for comparisons. Among 11- to 12-year-old players at baseline, a gradient of elite > club > dropout was suggested for size and function, although differences were not consistently significant. Elite players performed significantly better in only two of the four skills, dribbling and ball control. A gradient of elite > club > dropout was more clearly defined among 13- to 14-year-old players at baseline. Elite players were older chronologically and skeletally, larger in body size and performed better in functional capacities and three skill tests than club players and dropouts. Baseline task and ego orientation did not differ among dropouts and club and elite players at follow-up in either age group. The results suggest an important role for growth and maturity status, functional capacities, and sport-specific skills as factors in attrition, persistence, and moving up in youth soccer.